(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article, the question of stages of forming of reasons and necessities is exposed at students to physical self-perfection, values of a healthy way of in the comet of aksyobgycheskogo approach in pedagogical science. Indicated, that in this plan authority and positive example, style of conduct of teacher, social environment and options, acts important part in society.